Developments in surface magneto-optical Kerr effect setup for ultrahigh vacuum analysis of magnetic ultrathin films - SHVETS, IGOR; USOV, VICTOR; MURPHY, SHANE (My University, 2005)
We describe a surface magneto-optical Kerr effect (SMOKE) setup designed to study the magnetic properties of ultrathin films in ultrahigh vacuum (UHV). As in earlier systems, a crossed-poles electromagnet is used, which allows measurements in the longitudinal or polar configurations to be carried out without displacing the sample or changing the optical path. The poles are mounted in-vacuum, while the coils and yoke are mounted externally to obtain a higher magnetic field ( ~ 2.8?kOe). The width of the gap between the poles can be adjusted depending on the size of the sample. The performance of the instrument is demonstrated by measurements of the paramagnetic-ferromagnetic phase transition in a 2 ML Fe film grown on the Mo(110) surface.
PUBLISHED
Keywords: Surface Physics; thin films